KEY ISSUES ON LANDSCAPE PLANNING IN THE CONTEXT OF ENVIRONMENTAL SUSTAINABILITY - Festus, Ibimilua Adewale (European Scientific Journal, ESJ, 2014)
This paper presents key issues on landscape planning and environmental design. The paper is more descriptive than analytical and has the objective of bringing out the interrelationships between landscape planning and sustainable development. It begins by looking at the theoretical and conceptual issues in landscaping, sustainability and environmental impact design. It then goes on to assess the intensity and scale of environmental impacts from landscape planning. It argued that landscaping is a pre-requisite to environmental sustainability. Hence the paper asserted that unsustainable use of landscape elements leads to environmental problems like biodiversity loss, climate change, global warming, soil and coastal erosion, and pollution. The paper identifies the negative and positive impacts from landscape planning. Findings from the study show that the positive impacts outweigh the negative impacts. Hence, the paper proposed that sustainable landscape planning should be given a huge priority in development projects. The paper concludes by recommending that stakeholders should be actively involved in environmental decision making, policy formulation and implementation, for the achievement of the most desired environmental sustainability